Tylko mnie kochaj komedia romantyczna reżysera "Nigdy w zyciu!" Ryszarda Zatorskiego - Zieliński, Maciej 1971- (TVN, MTL Maxfilm, 2006)
Michael, a handsome architect, has to deal with three women who suddenly appear in his life. They turn his life upside down and Michael must choose the one who is the prettiest, the most tempting and most ideal. Which of the trio will hear him whisper "Love only me?
Breitbild 16:9
Original: Polen 2006
Untertitel: Englisch
Szenariusz i reżyseria: Ryszard zatorski ; z udziałem: Macieja Zakościelnego, Agnieszki Grochowskiej, Agniszki Dygant, Grażyny Szapołowskiej, Jana Frycza, Marcina Bosaka, Julii Wróblewskiej ; ze specjalnym udziałem: Danuty Stenki, Artura Zmijewskiego ; zdjęcja: Tomasz Dobrowolski ; kirownik produkcji: Ryszard Chutkowski ; scenografia: Anna Adamszek ; muzyka: Maciej Zieliński ; ... ; producenci: Tadeusz Lampka, Dariusz Gąsiorowski
Bonusmaterial: Kinotrailer und TV, Making of, Interviews mit Schöpfern, Galerie der Standbilder
Keywords: Man-woman relationships / Drama; Man-woman relationships; Foreign films; Motion pictures, Polish; Drama; Feature films; Romantic comedy films; Film; DVD-Video